UPAYA MENDAUR ULANG BOTOL BEKAS SEBAGAI IDE USAHA - Amelia Rosanti (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2024)
Waste is a major problem in developing countries, one of which is Indonesia. The existing waste will continue to increase every day and can pollute the environment. To reduce waste in Indonesia, efforts are needed to manage existing waste into new goods that have good selling value. One type of waste that can be recycled and has business value is used bitil. Students have an obligation to carry out community service. One of the services that students can do is by providing education on waste management into useful items that have selling value. This student dedication regarding waste which can become a business idea can be applied to high school students. At high school age, knowledge and ideas are needed to run a business. Students can be trained by conducting counseling. From this background, the author carried out a service entitled efforts to recycle used bottles as a business idea with the aim of knowing the process of recycling used bottles and the benefits of recycling used bottles. The method used is licensing, observation, program socialization, writing and training evaluation. The education was carried out with several activities, namely mapping sources of used bottles, collecting used bottles, separating used bottles, washing used bottles, cutting used bottles, washing, recycling processes and looking at business potential. This service was carried out at SMAN 1 PETIR. The results obtained are divided into three stages. In the first stage, students successfully carried out counseling in the form of choosing organic and non-organic waste. In the second stage, students are able to educate students about the importance of maintaining cleanliness and finally, students are able to teach students about business opportunities that can be made from recycled plastic bottle waste.